Antimicrobial, Antioxidant and Cytotoxic Activities of Citrus Hystrix DC. Fruits (Dhaka University Journal of Pharmaceutical Sciences, 2010)
DOI: 10.3329/dujps.v8i2.6035 Dhaka Univ. J. Pharm. Sci. 8(2): 177-180, 2009 (December)